Namibia’s vernacular architecture: insights towards the sustainable development of local communities - Maio, Rui; Martin, Elao; Sojkowski, Jon; Ferreira, Tiago Miguel (Ge-conservacion, 2017)
Vernacular architecture is commonly recognized as the fundamental expression of the world’s cultural diversity. Natural disasters, the lack of knowledge and awareness of local communities, the desire for modernization and the well-known globalization phenomenon are some of the most frequent evoked issues responsible for endangering the survival of vernacular heritage in Africa. Hence, this paper aims to address some of these issues by providing a detailed architectural and morphological characterization of the “Owambo” tribe, the largest cultural area of Namibia. With this case study, the authors aim to highlight the outstanding universal value of vernacular architectural heritage in Namibia and to raise awareness to the increasing need, not only the protection of these structures’ integrity but also for the preservation of such ancient and sustainable building techniques as a living heritage.